Does a greater training load increase the risk of injury and illness in ultramarathon runners? A prospective descriptive, longitudinal design - Craddock, Nicole (Division of Exercise Science and Sports Medicine, 2022)
Background: Ultramarathon running has become extremely popular over the years. Despite the numerous health benefits of running, there are also many negative effects of running such as increased risk of musculoskeletal injury and illness. Training loads imposed on an athlete should induce positive physiological adaptations to improve their performance. Monitoring of an athlete's training load has become extremely important in terms of injury prevention. Currently, the relationship between training loads and injury and illness incidence is uncertain. More research is needed in this field to minimise the risk of injury and illness and maximise performance in ultramarathon runners. Aim: To determine if there are any associations between injury and illness incidences and training loads among ultramarathon runners in the 12 week period preceding an ultramarathon event and the four week period after the event. Specific Objectives: - To describe the incidence rate of overall and region-specific running-related injuries in a population of ultramarathon runners in the 16 week period surrounding an ultramarathon event. - To describe the incidence rate of illness and illness-related symptoms in a population of ultramarathon runners in the 16 week period surrounding an ultramarathon event. - To describe the weekly and cumulative training parameters (training volume, training frequency, training intensity, training duration) of the injured and uninjured groups and the ill and healthy groups over the 16 week period. - To describe the weekly and cumulative absolute training load parameters (internal load, external load) of the injured and uninjured groups and the ill and healthy groups over the 16 week period. - To describe the weekly relative training load parameters (ACWR) of the injured and uninjured groups and the ill and healthy groups over the 16 week period. - To determine whether there are any significant differences between the injured and uninjured groups and the ill and healthy groups with regard to: a) mean training parameters; b) mean internal training load; and c) mean external training load, over the 16 week period. - To identify any significant associations between: a) absolute training load (internal training load; external training load) and injury and illness incidence; and b) relative training load and injury and illness incidence over the 16 week period. Methods: A prospective, descriptive, longitudinal study design was conducted in runners who were training for the 2019 Two Oceans Ultramarathon. One hundred and nineteen participants were recruited for this study and tracked over a period of 16 weeks (12 weeks leading up to the Two Oceans Ultramarathon event and for four weeks afterwards). Data was collected once a week via an online logbook. Training parameters measured included weekly average running distance, average duration, average frequency and average session RPE. Injury data included injury counts, the structure injured, the main anatomical location and time-loss from injury. Illness data included illness counts, the main illness-related symptoms and time-loss from illness. Results: The overall injury incidence proportion was 31%. The week after the ultramarathon race had the highest injury proportion of 7%. The overall injury incidence was 5 per 1000 training hours. The average time-loss due to injury was three training sessions missed. The overall illness incidence proportion was 66%. The week after the ultramarathon race also had the highest illness proportion of 22%. The overall illness incidence was 16 per 1000 training days. The average time-loss due to illness was three training sessions. A moderate significant negative association was found between external training load and injury (r=-0.56; p=0.025). No associations were found between internal training load and injury; or between internal and external training load and illness respectively. A significant relationship was found for external training load and injury incidence in weeks 5 to 8 for participants who ran less than 30km per week. A significant relationship was found for external training load and illness incidence in weeks 5 to 8, 9 to 12 and 13 to 16 for participants who ran less than 30km per week. A significant relationship was found between the ACWR of >1.5 and injury incidence in weeks 1 to 4, 5 to 8 and 13 to 16. A significant relationship was found between the ACWR of <0.5 and illness incidence in weeks 13 to 16. Conclusion: In conclusion a lower training load could potentially predispose to running-related injuries or the development of illness. Specifically, a weekly mileage of less than 30km per week may increase the risk of sustaining an injury or illness when training for an Ultramarathon event. An ACWR greater than 1.5 may increase the risk of injury in the subsequent week of training and an ACWR less than 0.5 may increase the risk of illness in the following week. Non-gradual changes to a weekly training load, whether increases or decreases, could increase the risk of incurring a running-related injury or illness. Maintaining an ACWR between 0.5 and 1.5 appears to be optimal in minimising the risk of sustaining a running-related injury or illness. We therefore recommend the use of both absolute and relative workloads in the monitoring of an athlete's training load with the aim of minimising injury and illness risk and maximising performance in ultramarathon runners.